PERAN KEPEMIMPINAN DALAM KEBERHASILAN STARTUP: INTEGRASI DYNAMIC LEADERSHIP, ORGANIZATIONAL AGILITY, DAN BUDAYA INOVASI - Hendrian Yonata; Yan Noviar Nasution; Surta Wijaya; Dadang Junaedi (Economicus : Jurnal Ekonomi dan Manajemen, 2025)
Startups have become the driving force behind digital economic innovation in the era of disruption. The success of a startup is not solely determined by technological advantages, capital availability, or market opportunities, but by the quality of leadership capable of managing uncertainty, fostering organizational agility, and instilling a vibrant culture of innovation. This article develops a conceptual and empirical study on the relationship between dynamic leadership, organizational agility, and innovation culture in startup success, integrating data and reflections from both the Indonesian and global contexts. Through a descriptive qualitative approach and cross-case analysis of Gojek, Tokopedia, Traveloka, as well as Tesla and Zoom as global comparatives, the research finds that dynamic leadership serves as a key catalyst in building organizational adaptive capacity. The results show that innovation culture acts as a mediator, strengthening the impact of dynamic leadership on startup success through enhanced organizational agilityd.